Planktonic Foraminifera biostratigraphy at the Jerissa area, (CES section in north-western Tunisia), and the impact of the Cenomanian-Turonian Oceanic Anoxic Event (OAE-2) on their assemblages - Soua, Mohamed; Zaghbib-Turki, Dalila (Anuário do Instituto de Geociências, 2006)
Abstract